2003
DOI: 10.1074/jbc.m303800200
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational Modifications of Three Members of the Human MAP1LC3 Family and Detection of a Novel Type of Modification for MAP1LC3B

Abstract: The molecular machinery required for autophagy is highly conserved in all eukaryotes as seen by the high degree of conservation of proteins involved in the formation of the autophagosome membranes. Recently, both yeast Apg8p and its rat homologue Map1lc3 were identified as essential constituents of autophagosome membrane as a processed form. In addition, both the yeast and human proteins exist in two modified forms produced by a series of post-translational modifications including a critical C-terminal cleavag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
209
3
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 265 publications
(228 citation statements)
references
References 31 publications
4
209
3
7
Order By: Relevance
“…8 Furthermore, MAP1LC3C is poorly expressed in tissues, showing a relative prevalence in placenta, lung and ovaries. 7 In our study we were able to detect the mRNA levels of LC3A in liver, kidney and lung mouse tissues and, furthermore, imunohistochemistry confirmed cytoplasmic localization of LC3A in these tissues. Among the three isoforms MAP1LC3A (or simply LC3A) is a well-defined autophagosomal marker with a conserved post-translational modification at the C-terminal Gly120.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…8 Furthermore, MAP1LC3C is poorly expressed in tissues, showing a relative prevalence in placenta, lung and ovaries. 7 In our study we were able to detect the mRNA levels of LC3A in liver, kidney and lung mouse tissues and, furthermore, imunohistochemistry confirmed cytoplasmic localization of LC3A in these tissues. Among the three isoforms MAP1LC3A (or simply LC3A) is a well-defined autophagosomal marker with a conserved post-translational modification at the C-terminal Gly120.…”
Section: Resultssupporting
confidence: 66%
“…The MAP1LC3B is expressed in heart, brain, skeletal muscle and testis and least expressed in the liver, where MAP1LC3A is most plentiful. 7 Also, MAP1LC3B is expressed highly in peripheral blood leukocytes in which MAP1LC3A mRNA is absent. 7 In contrast, Wu and coworkers reported that MAP1LC3A is abundant in heart, brain, skeletal muscle, lung and testis and undetectable in liver, pancreas, spleen and small intestine of rat tissues, whereas MAP1LC3B is expressed highly in liver, brain, skeletal muscle and testis but is undetectable in lung.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since knockdown of SRC-3 or MIF reduced Bcl-2 levels, but did not significantly affect apoptosis (Supplementary information, Figure S8), we investigated whether MIF regulated autophagy. Cleavage of the autophagy marker microtubule-associated protein 1 light chain (LC3) to LC3-I and conjugation of LC3-I to phosphatidylethanolamine to form LC3-II is an essential process for the formation of autophagosomal vacuoles [44][45][46][47][48][49]. As the levels of LC3-II are proportional to the extent of autophagic vacuole formation, we therefore examined the processing of LC3 as an indicator of autophagy activity.…”
Section: Mif Regulates Autophagymentioning
confidence: 99%
“…Briefly, 5 AL of the total 20 AL of reverse-transcribed product were used for PCR in 1Â PCR buffer containing 1.5 mmol/L MgCl 2 , 250 Amol/L deoxynucleotide triphosphates, 0.5 unit of Taq polymerase (Invitrogen/ Life Technologies), and 100 ng of TG2 primer (primer I, 5 ¶-TA-TGGCCAGTGCTGGGTCTTCGCC-3 ¶; primer II, 5 ¶-GGCTC-CAGGGTTAGGTTGAGCAGG-3 ¶) or PKCy primers (primer I, 5 ¶-CGAAGAGTTCATCCTCATCATA and primer II, 5 ¶-TTTC-TCACCCACCTCATCTG) or h-actin -specific primer (SigmaGenosys, Houston, TX). Semiquantitative RT-PCRs were done using different cycles of PCR (26,30,36) to find optimum PCR cycle that falls in the linear range of amplification. For the TG2 and PKC experiments, 30 PCR cycles were used.…”
Section: Rna Isolation and Rt-pcr Analysismentioning
confidence: 99%